Muscle metabolism during exercise with carbohydrate or protein-carbohydrate ingestion - Cermak, N. M.; Solheim, A. S.; Gardner, M. S.; Tarnopolsky, M. A.; Gibala, M. J. (Medicine & Science in Sports & Exercise, 2009)
Introduction: Ingesting protein (PRO) with CHO during prolonged exercise is purported to improve performance compared with CHO alone by altering the regulation of skeletal muscle energy provision. However, no study has directly investigated this issue. We tested the hypothesis that compared with CHO alone, coingestion of PRO would alter markers of metabolic control, including the magnitude of glycogen use and the net expansion of the tricarboxylic acid cycle intermediate pool, which has been linked to the capacity for oxidative energy delivery.